A COMPARATIVE STUDY ON TASK FEATURES IN LEARNING MANAGEMENT SYSTEM (LMS) - Mufliharsi, Risa (Universitas Muhammadiyah Tangerang, 2024)
his paper aims to analyze features in selected distance learning management systems in improving students' experiential learning through Flipped Classrooms and Task-Based Language Teaching for higher educational institutions. Learning through Flipped Classroom has enriched broad teaching-learning activities to strengthen students' concepts in independent learning. Positively, it is also developing students' electronic literacy through technology. The use of learning management systems not only improves students' activity but also helps construct students' learning experiences for understanding the nature of comprehension through various tasks. However, many lecturers are doubtful about selecting the Learning Management System appropriate to learning tools to facilitate students' work in doing tasks. Therefore, the paper compares four Learning Management Systems, namely Moodle, Chamilo, Efront, and Dokeos, based on features under various criteria and parameters to choose the right one. The result showed that Moodle fulfilled most criteria needed for a Task-Based Flipped Classroom in a Higher Educational Institution.Keywords: flipped classroom; learning management system; task-based language teaching; task featuresMakalah ini bertujuan untuk menganalisis fitur dalam beberapa sistem manajemen pembelajaran jarak jauh untuk digunakan dalam meningkatkan pengalaman belajar siswa melalui flipped classroom dan Task-based language teaching untuk institusi pendidikan tinggi. Pembelajaran melalui Flipped Classroom telah memperkaya kegiatan belajar mengajar yang luas untuk memperkuat konsep siswa dalam belajar mandiri. Penggunaan sistem manajemen pembelajaran jarak jauh tidak hanya meningkatkan aktivitas siswa tetapi juga membantu membangun pengalaman belajar siswa untuk memahami hakikat pemahaman melalui berbagai tugas. Positifnya, Penggunaan sistem manajemen pembelajaran jarak jauh juga mengembangkan literasi elektronik siswa melalui teknologi. Namun, banyak dosen yang ragu dalam memilih Learning Management System yang tepat sebagai perangkat pembelajaran untuk memudahkan pekerjaan mahasiswa dalam mengerjakan tugas. Oleh karena itu, makalah ini membandingkan empat Sistem Manajemen Pembelajaran, yaitu Moodle, Chamilo, Efront, dan Dokeos, berdasarkan fitur dengan berbagai kriteria dan parameter untuk memilih yang tepat. Hasilnya menunjukkan bahwa Moodle memenuhi sebagian besar kriteria yang dibutuhkan untuk Kelas Terbalik Berbasis Tugas di Perguruan Tinggi. Kata Kunci: flipped classroom; system manajemen pembelajaran; pembelajaran bahasa berbasis tugas; fitur tugas